2011
DOI: 10.1152/ajpgi.00530.2010
|View full text |Cite
|
Sign up to set email alerts
|

Association of PDZ-containing protein PDZD11 with the human sodium-dependent multivitamin transporter

Abstract: Nabokina SM, Subramanian VS, Said HM. Association of PDZcontaining protein PDZD11 with the human sodium-dependent multivitamin transporter. Am J Physiol Gastrointest Liver Physiol 300: G561-G567, 2011. First published December 23, 2010 doi:10.1152/ajpgi.00530.2010Intestinal absorption of biotin is mediated via the sodium-dependent multivitamin transporter (SMVT). Studies from our laboratory and others have characterized different aspects of the human SMVT (hSMVT), but nothing is currently known about protein(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
(39 reference statements)
3
18
0
Order By: Relevance
“…The proposed function of PDZD11, a ubiquitously expressed protein, was to provide a scaffold for these transmembrane proteins, by binding through its PDZ domain, to the PDZ-binding motif at their C terminus. Supporting this idea, depletion of PDZD11 reduced the cell surface expression of the sodium-dependent multivitamin transporter, as assessed by cell surface biotinylation assay (32). Other single PDZ proteins, such as MALS (mammalian homolog of , are implicated in intracellular transport and targeting of their partner proteins (38), and future studies should determine whether PDZD11 also plays this role, for example by promoting the efficient transport of PDZ-binding proteins such as nectins to the cell surface.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The proposed function of PDZD11, a ubiquitously expressed protein, was to provide a scaffold for these transmembrane proteins, by binding through its PDZ domain, to the PDZ-binding motif at their C terminus. Supporting this idea, depletion of PDZD11 reduced the cell surface expression of the sodium-dependent multivitamin transporter, as assessed by cell surface biotinylation assay (32). Other single PDZ proteins, such as MALS (mammalian homolog of , are implicated in intracellular transport and targeting of their partner proteins (38), and future studies should determine whether PDZD11 also plays this role, for example by promoting the efficient transport of PDZ-binding proteins such as nectins to the cell surface.…”
Section: Discussionmentioning
confidence: 98%
“…PDZD11 is also known as AIPP1 through its binding to the cytoplasmic tail of the Menkes copper ATPase ATP7A (31) and as an interactor of the sodium-dependent multivitamin transporter (32). The proposed function of PDZD11, a ubiquitously expressed protein, was to provide a scaffold for these transmembrane proteins, by binding through its PDZ domain, to the PDZ-binding motif at their C terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study, using yeast two-hybrid screening of a human intestinal cDNA library, has identified PDZD11 (PDZ domain-containing protein 11), a PDZ-containing protein, as an interacting partner with hSMVT [62]. The interaction between hSMVT with PDZD11 was confirmed further in vitro [by a GST (glutathione transferase) pull-down assay] and in vivo (by two-hybrid luciferase and co-immunoprecipitation assays), as well as by confocal imaging of living cells.…”
Section: Biotinmentioning
confidence: 99%
“…Furthermore, the interaction had a functional consequence in that co-expression of hSMVT with PDZD11 led to an increase in biotin uptake, whereas knocking down PDZD11 (with the use of gene-specific siRNA) led to an inhibition of uptake. Moreover, the PDZ-binding domain of the hSMVT polypeptide that interacts with PDZD11 was localized to the C-terminal tail of the transporter [62]. …”
Section: Biotinmentioning
confidence: 99%
“…Other studies have described the existence of an accessory protein, PDZD11, in human colonic epithelial cells that interacts with the SMVT (at the COOH terminus of the transporter) and affects its function and cell biology ( Fig. 1) (57). While another potential biotin transport system has been suggested in other tissues (108), the SMVT system appears to be the only system that operates in the mammalian gut.…”
Section: Production Of Wsv By Intestinal Microbiota and Their Absorptmentioning
confidence: 97%